ANALISIS MORFOMETRIK DAN SIFAT KUALITATIF WARNA BULU PADA PUYUH LIAR (Turnix suscitator atrogularis) DAN PUYUH DOMESTIKASI (Coturnix-coturnix japonica) - Reynal Parasian Hutagalung (Universitas Sumatera Utara, 2013)
ABSTRACT Research of morphological, morphometric, and the qualitative nature of colour feathers is the basis process of selection and breeding quail. This research aims to identify the main identifier on the size and shape of wild quail and qualitative traits of wild quail feather and domestication. This research used 20 wild quail and 20 domestication quail . Data were analyzed using Principal Component Analysis and Software Statistical Package for Social Science (SPSS) to determine the identifier the size and shape of organs both types of quail.The results showed that the primary identifier on the size of the external organs of wild quail is the longest fingers and organs form outside the main identifier is the length of the wing. The main identifier is the length of organ size in the small intestine and the main identifier is the long form of the mouth and neck. The main identifier the size of the outer parts of quail domestication is the length of the femur and tibia. The main identifier is the long form of the outer parts maxilla. The main identifier is the size of the organ in the liver and the identifier is the main form of long necks. Characteristic of the colour feathers wild quail is very different with domesticated. Wild quail males have yellowish brown neck, while the females are black. Male domesticated quail have dark brown neck, while the female is light brown. Wild quail has a beak and feet are gray while quail domestication has a yellow beak and feet. Keywords : Quail, morphology, morphometrics, the qualitative nature. ABSTRAK Tinjauan terhadap morfologi, morfometrik, dan sifat kualitatif warna bulu merupakan dasar di dalam proses seleksi dan pemuliaan burung puyuh. Penelitian ini bertujuan mengidentifikasi penciri utama ukuran dan bentuk serta sifat-sifat kualitatif warna bulu burung puyuh liar (Turnix suscitator atrogularis) dan domestikasi. Burung puyuh domestikasi yang diteliti sebanyak 20 ekor dan burung puyuh liar yang diteliti sebanyak 20 ekor. Data dianalisis menggunakan Analisis Komponen Utama dengan bantuan Software Statistical Package for the Social Science (SPSS) untuk menentukan penciri utama ukuran dan bentuk organ tubuh kedua jenis burung puyuh. Hasil penelitian menunjukkan bahwa penciri utama ukuran organ luar pada burung puyuh liar adalah jari ketiga dan penciri utama bentuk organ luar adalah panjang sayap. Penciri utama ukuran organ dalam adalah panjang usus halus dan penciri utama bentuk adalah panjang mulut dan leher. Penciri utama ukuran organ luar pada burung puyuh domestikasi adalah panjang femur dan tibia. Penciri utama bentuk organ luar adalah panjang maxilla. Penciri utama ukuran organ dalam adalah organ hati dan penciri utama bentuk adalah panjang leher. Sifat-sifat kualitatif warna bulu pada kedua jenis burung puyuh sangat berbeda. Puyuh liar jantan memiliki leher berwarna cokelat kekuningan, sedangkan leher pada betina berwarna hitam. Puyuh domestikasi jantan memiliki leher berwarna cokelat tua sedangkan leher pada betina berwarna cokelat muda. Puyuh liar memiliki paruh dan kaki berwarna abu-abu sedangkan puyuh domestikasi memiliki paruh dan kaki berwarna kuning. Kata kunci : Puyuh, morfologi, morfometrik, sifat kualitatif.